Effects of dietary extrusion on the performance and apparent ileal digestion of broilers: a meta-analysis - Sazli Tutur Risyahadi; Heri Ahmad Sukria; Yuli Retnani; Indah Wijayanti; Anuraga Jayanegara; Novia Qomariyah (Italian Journal of Animal Science)
The present research aimed to evaluate the effects of extruded feed ingredients on the growth performance and apparent ileal digestion of broilers using a meta-analysis. The database was developed based on 30 studies comprising 150 data points. The data were analysed using the OpenMEE software, considering the extrusion of feed ingredients as fixed effects and individual studies as random effects. Results showed that the extruded feed ingredients enhanced weight gain (p < 0.01) and enhanced the feed conversion ratio (p < 0.001) of broiler chickens as compared to the un-extruded feeds, but no effect was observed for the feed intake parameter. The digestibility of dry matter, crude protein, and crude fat were significantly higher for the extruded feeds (p < 0.05). In terms of amino acid digestibility, the current meta-analysis also demonstrated that extruded feed ingredients had significantly higher (p < 0.05) digestibility in Ala, Leu, Met, Phe, Thr, Try, Tyr, and Val than those of the un-extruded feeds. In conclusion, extrusion can improve the production performance of broilers, and it increases some nutrient and amino acid digestibility.HIGHLIGHTS Extrusion of feed ingredients increased weight gain and enhanced the feed conversion ratio of broilers. Digestibility of dry matter, crude protein and crude fat was higher for the extruded than that of the un-extruded feed. The extruded feed ingredients had higher digestibility amino acids in Ala, Leu, Met, Phe, Thr, Try, Tyr and Val than those of the un-extruded feeds.